I think it’s 90% cuz it’s 45/50 therefore 90/100
Answer:
B
Step-by-step explanation:
To rewrite the equation x + y + 3 = -2x + 4y + 18, first combine like terms.
x + y + 3 = -2x + 4y + 18
3x - 3y + 3 = 18
3x - 3y = 15
This is the standard form.
It can also be simplified by dividing each term by 3 to x - y = 5.
Answer:
![A' =(-y,x)](https://tex.z-dn.net/?f=A%27%20%3D%28-y%2Cx%29)
Step-by-step explanation:
Given
Represent point A as thus;
![A = (x,y)](https://tex.z-dn.net/?f=A%20%3D%20%28x%2Cy%29)
Required
Determine the new position of A, when rotated counterclockwise
The new position will be denoted as A'
When a point is rotated counterclockwise, we start by switching the positions of x and y as follows:
![Pos = (y,x)](https://tex.z-dn.net/?f=Pos%20%3D%20%28y%2Cx%29)
Then, y is negated to give A'
![A' =(-y,x)](https://tex.z-dn.net/?f=A%27%20%3D%28-y%2Cx%29)